Quantification of mycotoxins in vegetable oil by UPLC-MS/MS after magnetic solid-phase extraction. Issue 7 (3rd July 2017) - Zhao, Yan; Wan, Li-Hong; Bai, Xiao-Lin; Liu, Yi-Ming; Zhang, Feng-Ping; Liu, Yao-Min; Liao, Xun
ABSTRACT: The detection of mycotoxin contamination in foodstuffs is highly significant for public health. Herein we report an analytical method based on magnetic solid-phase extraction (MSPE) and UPLC-MS/MS for the simultaneous determination of mycotoxins, including fumonisins B1 (FB1 ), zearalenone (ZON) and ochratoxin A (OTA), in vegetable oil. Magnetic nanoparticles coated with double layers of silicon dioxide were synthesised and found to be an effective MSPE adsorbent for mycotoxins. The proposed MSPE procedure serves not only for sample clean-up but also for mycotoxin enrichment that enhances greatly the assay's sensitivity. Under the selected MSPE conditions, linear matrix-matched calibration curves were obtained for mycotoxins in a concentration range from 0.178 to 625 μg kg –1 . The limits of detection were 0.210 μg kg –1 for FB1, 0.0800 μg kg –1 for OTA and 1.03 μg kg –1 for ZON. The proposed MSPE UPLC-MS/MS method was applied for the determination of mycotoxins in vegetable oil samples, including maize oil, rapeseed oil and soybean oil. ZON was detected in a maize oil at 101 μg kg –1, which is below the European Union limit of 200 μg kg –1 in foodstuffs. GRAPHICAL ABSTRACT: